Original paperAnalysis of selected recurrence risk factors after treatment of head and neck basal cell carcinoma - Szewczyk, Mateusz P.; Pazdrowski, Jakub; Dańczak-Pazdrowska, Aleksandra; Golusiński, Paweł; Majchrzak, Ewa; Łuczewski, Łukasz; Marszałek, Sławomir; Silny, Wojciech; Golusiński, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction : Basal cell carcinoma (BCC) is the most common type of non-melanoma malignant skin tumors. Eighty-five percent of all cases are located on the skin of the head and neck. The risk of recurrence after surgery is estimated at 5–15%. Aim: To evaluate the selected risk factors for recurrence after surgical treatment of head and neck BCC at the Department of Head and Neck Surgery in the Greater Poland Cancer Centre of the Poznan University of Medical Sciences. Material and methods : A retrospective analysis was made of patients treated at the Department of Head and Neck Surgery in the Greater Poland Cancer Centre of the Poznan University of Medical Sciences in 2007–2012 for BCC of the head and neck region. The study covered 312 patients: 198 males (63%) and 114 females (37%), aged 32–96 years. Results : In the study group of 312 tumors, recurrence after initial treatment in this Centre was diagnosed in 18 patients (9%), whereas in patients who were previously operated elsewhere, recurrence was found in 22 cases (17%). The nodular type was the most common BCC type in the study group and concerned 175 patients (56%). The most numerous group (114; 37%) in this study group comprised patients with external nose and cheek tumors. Conclusions : The importance of preoperative biopsy to assess the histological type as a routine treatment of patients with BCC is essential. Ultrasound evaluation to assess the exact size and depth of tumor invasion should also be implemented.